1977
DOI: 10.1093/infdis/136.supplement_3.s722
|View full text |Cite
|
Sign up to set email alerts
|

Summary of Clinical Trials of Influenza Virus Vaccines in Adults

Abstract: Trials in approximately 3,900 adults were conducted with influenza A/New Jersey/76, A/Victoria/75, and B/Hong Kong/72 virus vaccines. Subjects were observed following a standard protocol, and serologic testing was performed in a single laboratory. The data indicate that prior experience of the population with earlier influenza viruses ("priming") is a determinant in response to vaccination. Thus, participants older than 25 years showed good serologic response following a single inoculation of A/New Jersey/76 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(48 citation statements)
references
References 8 publications
4
44
0
Order By: Relevance
“…A second vaccination might be effective. Previous studies [25][26][27][28][29] have suggested that 2 doses of vaccine are required to elicit a protective immune response in populations that are immunologically naïve to a new influenza strain. One study 10 reported that immune responses in the elderly could be substantially boosted by a second dose of vaccine-among subjects ≥61-y-old who received a 15-μg dose of unadjuvanted A(H1N1)pdm09 vaccine, the seroprotection proportion was 79.1% at 21 d after the first dose, and 93.3% at 14 d after the second dose (35 d after first dose).…”
Section: Discussionmentioning
confidence: 99%
“…A second vaccination might be effective. Previous studies [25][26][27][28][29] have suggested that 2 doses of vaccine are required to elicit a protective immune response in populations that are immunologically naïve to a new influenza strain. One study 10 reported that immune responses in the elderly could be substantially boosted by a second dose of vaccine-among subjects ≥61-y-old who received a 15-μg dose of unadjuvanted A(H1N1)pdm09 vaccine, the seroprotection proportion was 79.1% at 21 d after the first dose, and 93.3% at 14 d after the second dose (35 d after first dose).…”
Section: Discussionmentioning
confidence: 99%
“…Two doses of inactivated virus vaccines are usually recommended to immunize naïve individuals for adequate protection due to their relatively low immunogenicity (20). Therefore, development of a single-dose protective and safe vaccine would have significant advantages for application to humans.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, data from recent p-H1N1 vaccine trials suggest that a large segment of the population has been exposed to an influenza virus that "primed" individuals such that only one dose of the novel pandemic vaccine is sufficient to elicit a protective antibody titer (7)(8)(9)(10). This observation was unexpected, because studies conducted in the 1970s had shown that two doses of vaccine were needed to immunize a naïve population (11).…”
mentioning
confidence: 99%